Animasi Motion Graphic Safety Induction di Wilayah Universitas Pembangunan Nasional “Veteran” Jawa Timur untuk Mencegah Terjadinya Kecelakaan Kerja - Aulia Devi Rachmania (Jurnal Nawala Visual, 2023)
Workplace accidents in Indonesia are a significant problem, with increasing incidents each year. This can adversely affect productivity in addition to resulting in fatalities and material losses. A good culture of Occupational Health and Safety (OHS) is necessary to reduce workplace accidents. One way to implement an OHS culture is through the implementation of safety induction. Universitas Pembangunan Nasional "Veteran" Jawa Timur, one of Indonesia's universities, needs to implement safety induction to prevent workplace accidents. In addition to being given orally or through training, safety induction can also be given through media in the form of motion graphic animated videos. Motion graphic animated safety induction media is designed as a communication medium that is attractive, persuasive, and easy to understand. The data collection technique uses primary and secondary data using questionnaire dissemination, observation, interviews, and literature studies. From the data collected, data analysis is carried out using qualitative and quantitative techniques. Qualitative data techniques use the 5W+1H analysis to determine the unique selling proposition. Quantitative data techniques refer to questionnaire results using descriptive statistical analysis, frequency distribution, and central tendency. The results of this method produce verbal and visual concepts that will be implemented in the design of motion graphic animated safety induction videos in the area of Universitas Pembangunan Nasional "Veteran" Jawa Timur.